Provision of fertility services for women at increased risk of complications: Ethics opinion - Nalini Mahajan; Duru Shah; Madhuri Patil (Wolters Kluwer Medknow Publications, 2018)
Certain medical conditions can increase the risk to the mother during pregnancy. This can increase the risk of maternal morbidity or severe morbidity. If pregnancy is decided upon after expert counseling, a multidisciplinary team should provide care.